2013
DOI: 10.1002/app.39168
|View full text |Cite
|
Sign up to set email alerts
|

Low percolation threshold in polycarbonate/multiwalled carbon nanotubes nanocomposites through melt blending with poly(butylene terephthalate)

Abstract: Here, we demonstrate an easy method for the preparation of highly electrically conductive polycarbonate (PC)/multiwalled carbon nanotubes (MWCNTs) nanocomposites in the presence of poly(butylene terephthalate) (PBT). In the presence of MWCNTs, PC and PBT formed a miscible blend, and the MWCNTs in the PC matrix were uniformly and homogeneously dispersed after the melt mixing of the PC and PBT-MWCNT mixture. Finally, when the proportion of the PC and PBT-MWCNT mixture in the blend/MWCNT nanocomposites was change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 59 publications
4
52
0
Order By: Relevance
“…The close to 2.0 critical exponent t (1.96) was consistent with predictions from the statistical percolation theory for a three-dimensional conducting network in an insulating matrix [20,38,39]. The low p c in this study (0.28 vol.% or 0.50 wt.%) is similar to those observed in other successful studies on PC-based NCs obtained by both melt processing and sonication [40][41][42]. The low p c value indicates that in PC-based NCs, the interactions between the polymer and the MWCNT are more significant than the method used to obtain the NC.…”
Section: Mwcnt Content For Electrical Percolationsupporting
confidence: 91%
“…The close to 2.0 critical exponent t (1.96) was consistent with predictions from the statistical percolation theory for a three-dimensional conducting network in an insulating matrix [20,38,39]. The low p c in this study (0.28 vol.% or 0.50 wt.%) is similar to those observed in other successful studies on PC-based NCs obtained by both melt processing and sonication [40][41][42]. The low p c value indicates that in PC-based NCs, the interactions between the polymer and the MWCNT are more significant than the method used to obtain the NC.…”
Section: Mwcnt Content For Electrical Percolationsupporting
confidence: 91%
“…The polymer nanocomposites material is an innovative product having nanofillers dispersed in the matrix of polymers, and has received much interest recently. Significant efforts are underway to control the nano‐structures via innovative synthetic approaches with excellent antimicrobial properties, increased biocompatibility and potential for wound management.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical percolation threshold was achieved at 2.9 wt% of MWCNTs, and maximum EC (10 −3 S/cm) was obtained at 7 wt% MWCNTs loading. Maiti et al demonstrated a method of preparation of highly conductive PC/MWCNT composites in the presence of PBT. The electrical percolation was obtained at 0.21 wt% loading of MWCNTs with EC approximately 10 −9 S/cm.…”
Section: Pc/cnt Nanocompositesmentioning
confidence: 99%